2020
DOI: 10.1136/jitc-2020-001293
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 inhibitor inducing exosomal miR-34a-5p expression mediates the cross talk between cardiomyocyte and macrophage in immune checkpoint inhibitor–related cardiac dysfunction

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) have been an important therapeutic advancement in the field of cancer medicine. Recent reports provided greater insights into the cardiovascular adverse events, which prohibited the use of ICIs. Cardiovascular adverse events occur in different forms, such as myocarditis and cardiomyopathy, myocardial fibrosis, heart failure and pericardial disease. Cardiac aging overlapped with the occurrence of some cardiac diseases. Exosomes mediate cell–cell cross talk in cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Xia et al have characterized the mechanism of miR-34a-5p-induced cardiac senescence-related injury. It is shown that miR-34a-5p serves as an exosomal transfer RNA and the inhibition of miR-34a-5p mitigated the pro-senescent effect in cardiomyocytes and subsequently alleviated the irreversible cell cycle arrest ( Xia et al, 2020 ). miR-34a-5p is also found involved in regulating the switch between senescence and apoptosis in non-small cell lung cancer ( Gupta et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al have characterized the mechanism of miR-34a-5p-induced cardiac senescence-related injury. It is shown that miR-34a-5p serves as an exosomal transfer RNA and the inhibition of miR-34a-5p mitigated the pro-senescent effect in cardiomyocytes and subsequently alleviated the irreversible cell cycle arrest ( Xia et al, 2020 ). miR-34a-5p is also found involved in regulating the switch between senescence and apoptosis in non-small cell lung cancer ( Gupta et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs also play an important role in ICI-induced cardiac injury. Specifically, the PD-1 inhibitor promote a large amount of miR-34a aggregation in cardiomyocytes by regulating the miR-34a/KLF4 and miR-34a/Pnuts signaling pathways to induce myocardial inflammation and promote myocardial aging ( 100 , 101 ). miRNAs are therefore potential therapeutic targets for ICI-induced cardiac injury.…”
Section: Emerging Biomarkersmentioning
confidence: 99%
“…Interestingly, ncRNAs might also mediate side effects of ICI treatment. Xia et al revealed that ICIs induce exosomal trafficking of miR-34a-5p from macrophages to cause cardiac injury in vivo [ 320 ]. However, few studies have focused on the direct alterations of ncRNA profiles during ICI treatment, which might become a hot field in the near future.…”
Section: Noncoding Rnas Bridge Metabolites and Pro- Or Antitumor Immunitymentioning
confidence: 99%